FORHUM 2021
DOI: 10.35766/j.forhum2021.04.03.3
|View full text |Cite
|
Sign up to set email alerts
|

“Mi Mestre no es brasileño”: Sobre la autenticidad y legitimidad de la capoeira en México

Abstract: Griffith propone los marcadores de autenticidad como formas de capital cultural que permiten ganar legitimidad en el campo social de la capoeira. Entre ellos, destaca el grado de Mestre como último marcador de autenticidad/legitimidad. Pese a la globalización de la práctica, la literatura reporta la existencia de pocos Mestres no-brasileños, especialmente en las regiones del Norte Global. En este contexto, el caso de México es atípico por contar con un número equiparable de Mestres mexicanos y brasileños. Este… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…these are not based in Brazil, like João Grande or Acordeon. Similarly, my analysis of the Mexican case [Contreras Islas 2021] has shown that great Brazilian are more likely to support the independent work of non-Brazilian teachers who represent a capoeira-community with a high standard of capoeira. In such cases, a great might praise the teacher with a high degree as a way to legitimize the work of the community as a whole, even if it is an independent project.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…these are not based in Brazil, like João Grande or Acordeon. Similarly, my analysis of the Mexican case [Contreras Islas 2021] has shown that great Brazilian are more likely to support the independent work of non-Brazilian teachers who represent a capoeira-community with a high standard of capoeira. In such cases, a great might praise the teacher with a high degree as a way to legitimize the work of the community as a whole, even if it is an independent project.…”
Section: Discussionmentioning
confidence: 85%
“…In this sense, the studies conducted by Lube Guizardi and Ypeij [2016], as well as Owen and De Martini Ugolotti [2019] suggest that acquiring legitimacy becomes all the more difficult the further a falls away from stereotypical markers of authenticity [Griffith 2013]. In another work, I have studied the strategies followed by the two Mexican with an independent capoeira-project to gain legitimacy within the field of the practice despite lacking the above-mentioned stereotypical markers [Contreras Islas 2021]. Since most in the North are also lacking these kind of markers, it might be in their own interest to learn about the experiences of their southern peers.…”
mentioning
confidence: 99%